Alkali pretreatment method of dairy wastewater based grown Arthrospira platensis for enzymatic degradation and bioethanol production. (15th December 2022) - Manmai, Numchok; Balakrishnan, Deepanraj; Obey, Gotore; Ito, Nobutaka; Ramaraj, Rameshprabu; Unpaprom, Yuwalee; Velu, Gomathi
Graphical abstract: Highlights: A. platensis has the capability and potential to be used as a bioethanol feedstock. The chemical concentration and pretreatment time affected the sugar yield. Enzyme activity of Trichoderma sp. produced sugar is similar to using the pure enzyme. The use of algae to convert wastewater into renewable energy is becoming increasingly popular. Abstract: Owing to increasing gasoline demand and fossil fuel depletion. Biofuel is increasingly being produced using an alternative source, such as algae. Microalgae is one such promising biofuel-generating solution. This investigation used the Response Surface Methodology (RSM), focusing on Central Composite Design to improve the chemical pretreatment conditions for the microalgae ( Arthrospira platensis ). The significant influence of sodium hydroxide (NaOH) concentration and pretreated time on sugar yield and pretreatment processes were optimized using CCD. Pretreatment parameters such as duration (1 to 3 days) and NaOH concentrations (1 to 3 % (w/v)) accumulated in the pretreatment model. Following the pretreatment stages, the microalgae biomass was digested with a cellulase enzyme and Trichoderma sp. under three conditions cellulase enzyme 2 %, Trichoderma sp. 2 %, and cellulase enzyme 1 % combined with Trichoderma sp. 1 %. The combinations were incubated at 30 °C for 1, 2, and 3 days, transferring to fermentable sugar for Saccharomyces cerevisiae TISTR5020 to use in bioethanol fermentation.